The Protective Effect of Conditioning on Noise-Induced Hearing Loss Is Frequency-Dependent - Akram Pourbakht; Azadeh Imani (Acta Medica Iranica, 2012)
We compared the extent of temporary threshold shift (TTS) and hair cell loss following high level 4 kHz noise exposure with those preconditioned with moderate level 1 and 4 kHz octave band noise. Fifteen Male albino guinea pigs (300- 350 g in weight) were randomly allocated into three groups: those exposed to 4 kHz octave band noise at 102 dB SPL (group 1, n=5); those conditioned with 1 kHz octave band noise at 85 dB SPL, 6 hours per day for 5 days, then exposed to noise (group 2, n=5); those conditioned with 4 kHz octave band noise at 85 dB SPL, then exposed to noise (group 3, n=5). An hour and one week after noise exposure, threshold shifts were evaluated by auditory-evoked brainstem response (ABR) and then animals were euthanized for histological evaluation. We found that TTS and cochlear damage caused by noise exposure were significantly reduced by 1 kHz and 4 kHz conditioning (P<0.001). We also showed that 4 kHz protocol attenuates noise- induced TTS but no significant TTS reduction occurred by 1 kHz conditioning. Both protocol protected noise-induced cochlear damage. We concluded that lower tone conditioning could not protect against higher tone temporary noise-induced hearing loss, thus conditioning is a local acting and frequency-dependent phenomenon.